DEVELOPING VOCABULARY ANIMATION GAME APPLICATION FOR PRONOUNCIATION AT PELITA KASIH LAWANG KINDERGARTEN - Adi; Christina Retna Ningrum; Trisnian Ifianti (UIBU, 2022)
The purpose of developing illustrated vocabulary animation game media for kindergarten – A students at Pelita Kasih Lawang Kindergarten is that early childhood can concentrate and understand the content of the material so that they are able to repeat simple words with correct pronunciation. Early childhood is also expected to be able to repeat words that have been listened to friends and teachers. Researchers compiled an animated vocabulary game media developer pictured in learning English, by making a Research and Development (R&D) development research design, which is research used to produce certain products, and test the validity of these products. This Research and Development procedure is an adaptation of Sugiono's theory (2011 : 297), namely : 1) Potential and Problems, 2) Data Collection, 3) Product Design, 4) Design Validation, 5) Usage Trial, 6) Product Revision, 7) Product Trial, 8) Design Revision. Product Trial, 8) Design Revision. The data analysis technique used is qualitative and quantitative analysis in the form of percentages. The results of this research and development obtained are : 94.44% of the learning expert validation results, 96.15% of the media expert validation results, 91.11% of the small group trial results, and 95.68% of the field trial results. Based on these results, the development of animated media in language learning is classified as feasible to use. Based on the validation results, observations on small group trials and field trials, it can be concluded that the development of animated media in language learning is very interesting, fun, and easy to use. It is hoped that the results of the development of animated media in language learning can be developed even better, more effective, and right on target. So that it can be utilized according to the needs and achieve the goals of early childhood language learning.